Effectiveness Of Classroom Learning And Self Regulated Learning Using Ecuator Application In English Learning For Staffs Of Kejaksaan Negeri Kuantan Singingi - Sri Chairani (Lembaga Penelitian Pengabdian Kepada Masyarakat dan Dakwah Islamiyah Universitas Islam Kuantan Singingi, 2021)
Technology and language are important thing in era of Industrial Revolution 4.0. They become important points to improve skill, especially human resource skill in English language. English language skill is needed to human resource development and to get the best career. Kejaksaan Negeri Kuantan Singingi is a government office of the counsel for the prosecution in Kuantan Singingi, it conducts the effort to attain the goal, it is the human resources development to increase performance quality the staff of Kejaksaan Negeri Kuantan Singingi. One of them is improving English skill in public service at front liner office of Kejaksaan Negeri Kuantan Singingi by giving trainee for the staffs to learn English. There are two methods for the staff of Kejaksaan Negeri Kuantan Singingi to learn and improve English. They are classroom learning was been teaching by the tutor, and self regulated learning by using the media Ecuator Application (English Course Application for Prosecutor). This research used qualitative methods. It aimed to find the effectiveness learning in the class and use the ecuator as the media. The result can be conclude that learning in the classroom by the tutor more effective than self regulated learning by using ecuator application in percentage about 65% for classroom learning and 20% for SRL using ecuator application as the media.